1996
DOI: 10.1021/ma951054+
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Generation of Conducting Patterns in Polybutadiene Films

Abstract: Certain polydiene rubbers can be doped by iodine to become electrically conducting. In particular, the conductivity of trans-1,4-polybutadiene can be increased by 8 orders of magnitude upon conjugation and self-doping by iodine at room temperature, whereas cis-1,4-polybutadiene cannot be made conducting by reaction with iodine under the same conditions. cis-1,4-Polybutadiene, however, can be converted into the trans-isomer by UV irradiation. On the basis of these previous findings, we have developed a simple a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 27 publications
(84 reference statements)
2
26
0
Order By: Relevance
“…However, cis-1,4-polybutadiene can be photoisomerized into the trans-isomer, and the isomerized material is then amenable to ªI 2 -dopingº. On the basis of this finding, we were able to create conducting micro-patterns in the nonconducting cis-1,4-polybutadiene film through a photolithographic method (see section beloẁ Photolithographic patterning of conjugated polymers') [361,362].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, cis-1,4-polybutadiene can be photoisomerized into the trans-isomer, and the isomerized material is then amenable to ªI 2 -dopingº. On the basis of this finding, we were able to create conducting micro-patterns in the nonconducting cis-1,4-polybutadiene film through a photolithographic method (see section beloẁ Photolithographic patterning of conjugated polymers') [361,362].…”
Section: Methodsmentioning
confidence: 99%
“…In this context, we have recently found that by using a microlithographic mask, cis-1,4-polybutadiene films can be photoisomerized into the trans-isomer in a patterned fashion without significant lateral diffusion [361,362]. As a result, only the photoisomerized regions are capable of generating conjugated double bonds (subsectioǹ Conjugated Polymers from Nonconjugated Precursor Polymers') upon exposure of the entire polybutadiene film to iodine at room temperature, resulting in the formation of conducting patterns in an insulating matrix of iodinated cis-1,4-polybutadiene.…”
Section: Advanced Microfabrications Of Oriented and Patterned Conjugamentioning
confidence: 99%
See 1 more Smart Citation
“…Dai et al [306] imputed the behavior difference between the two isomeric polymers to intramolecular properties, rather than the intermolecular packing, and suggested that the actual doping be better termed "an iodine mediated con jugation reaction". However, it was possible to create this conjugation by either photoirradiating iodinated poly(cis 1,4butadiene) or isomerizing poly(cis1,4butadiene) into poly(trans1,4butadiene), by exposure to UV irradiation in the presence of a photosensitizer such as diphenyl disulfide, followed by iodine doping [311], or by heating the iodinedoped poly(cis1,4butadiene) at 60°C for a time longer than 22 h [306]. The heatinduced conjugated I 2 poly(cis1,4butadiene) was then found to develop CTC involving long polyene sequences.…”
mentioning
confidence: 99%
“…1,2 In particular, the micro-lithographic formation of conducting patterns is a key prerequisite for various practical applications, such as in integrated circuits, field-effect transistors, multichannel molecular recognition, region-specific cell growth or protein fixation, optical memory storage devices, and electroluminescent and electrochromic displays. [3][4][5][6][7][8][9][10][11] Several methods, including top-down and bottom-up patterning of polymers, have been suggested for the generation of conducting patterns 12 (e.g., plasma etching, micromolding, photolithography, printing techniques, self-assembly of block copolymers, and instability-induced patterning). These methods lead to increased control over the pattern resolution and conductivity, rendering them highly valuable methods for various micro-to nano-technological applications.…”
Section: Introductionmentioning
confidence: 99%